Suicide risk and crises suffered in the context of COVID-19, mediated by interpersonal family communication (2023)
Objective To analyze the relationship between suicidal ideation and the concerns or affectations perceived at the family, economic and health levels during the first year of the COVID-19 pandemic in Colombia, and the mediating role of family communication. Method Participants were obtained through cluster sampling and quotas, resulting in 660 Colombians (Z=1.96; variance=0.25; error=3.9%), who answered a questionnaire consisting of three reliable scales between November 1 and 30, 2020, after providing informed consent. Binary logistic regression was used to evaluate the concerns or affectations that most influenced suicidal ideation during this period. Results Thirty-five percent of the Colombian participants presented a high level of suicidal ideation. The concerns or affectations that most strongly explain this level come from the realm of health and intrafamily relationships. The effect of health concerns or affectations on suicidal ideation decreases by up to 32.4% when family communication is open. Likewise, when this type of positive communication is present, the effect of the concerns or affectations perceived in the family, such as breakdowns, distancing, and crisis of coexistence, on suicidal ideation decrease between 29.1% and 70.1%. Conclusion Open family communication is a protective factor for mental health in crisis contexts because it can contribute to preventing suicide and alleviate to the concerns or affectations generated by COVID-19. Therefore, it is necessary to strengthen mental health programs through a communicative approach aimed at promoting assertive family dialog to achieve greater attention and openness to talk about concerns and affectations suffered